Religious movements in South Asia, 600-1800 - Lorenzen, David N (New Delhi ; Oxford : Oxford University Press, 2005)
This volume brings together eleven key essays that debate how the religious and worldly aims of religions movements in premodern South Asia have been linked and how their ideologies, social bases, and organizational structures both continued and changed over the course of time
Introduction / David N. Lorenzen 1 I Alvars and Nayanars 45 1 From Devotion and Dissent to Dominance: The Bhakti of the Tamil Alvars and Nayanars / R. Champakalakshmi 47 2 Social Mobility and Medieval South Indian Hindu Sects / Burton Stein 81 II Conversion to Islam 103 3 Approaches to the Study of Conversion to Islam in India / Richard M. Eaton 105 4 The Rishi Movement as a Social Force in Medieval Kashmir / Mohammad Ishaq Khan 128 III Rama and the Muslims 151 5 Ramayana and Political Imagination in India / Sheldon Pollock 153 6 Anachronism of the Political Imagination / Brajadulal Chattopadhyaya 209 7 The Founding of the Ramanandi Sect / Richard Burghart 227 IV Kabir and the Sants 251 8 The Times and their Need / P. D. Barthwal 253 9 Kabir's Place in Indian Religious Practice / Hajariprasad Dvivedi 269 V Historical Overviews 289 10 Towards a New Perspective / Krishna Sharma 291 11 Imagined Religious Communities?: Ancient History and the Modern Search for a Hindu Identity / Romila Thapar 333 Index 360 Notes on Contributors
Originally published , 2004 ; published in Oxford India paperbacks, 2005
Includes bibliographical references and index
Keywords: South Asia -- Religion